Critical Appraisal Worksheets for Integration Into an Existing Small-Group Problem-Based Learning Curriculum - Jessica O'Neil; Colleen Croniger (Association of American Medical Colleges, 2018)
Introduction Since medical students matriculate with a diversity of backgrounds, there can exist a disparity in student ability to critically appraise health science literature. To address this, we developed a critical appraisal exercise and integrated it into the first-year problem-based learning (PBL) curriculum at Case Western Reserve University School of Medicine. Methods For 8 weeks, first-year medical students read a weekly preselected health science literature article relating to the content of their PBL curriculum and completed a critical appraisal worksheet consisting of questions regarding study design and result interpretation. Students discussed the article and worksheet within PBL small groups. Faculty facilitators were given the critical appraisal worksheet answer key, which students later gained access to after the discussion. To measure changes in critical appraisal skills, a voluntary questionnaire based on the Berlin questionnaire, a validated tool for measuring knowledge and skills in evidence-based medicine, was administered before and after the 8-week intervention. Results Using paired Student t tests, we found that the students who completed both questionnaires (N = 60) showed an average improvement of 4% (p = .03). Students who scored at or below the 50th percentile on the preintervention questionnaire showed an average improvement of 12% (p = .002). Discussion These critical appraisal worksheets are easily adaptable to an existing PBL curriculum and are an effective tool for improving and teaching critical appraisal skills in those students who will benefit most.